209 'How rare do we dare' – hickam's dictum taken to the extreme. Issue 12 (14th November 2019) - Bunting, EE; Lunn, MP
Abstract : Solitary CNS Lymphomatoid granulomatosis (LG), a rare lymphoproliferative disorder, was discovered in a patient collecting rare neurological disorders. A patient diagnosed with Charcot-Marie-Tooth type 4C (SH3CT2) and Myasthenia Gravis, treated with mycophenolate, presented with musical hallucinosis, described as choral music occurring in short bursts. Investigations deemed this secondary to hearing loss. Neuro-imaging revealed a cerebellar cavernoma and a developmental venous anomaly, thought to be incidental. A rapidly expanding, right frontal lesion was noted on subsequent imaging. Biopsy of this lesion revealed a florid inflammatory infiltrate composed of small lymphocytes, macrophages and non-caseating granulomata. Immunohistochemical staining for CD20 showed moderate numbers of B-lymphocytes, positive for Epstein Barr virus-encoded small RNA, suggesting a diagnosis of LG. Immunosupression is a risk factor for EBV mediated lymphoproliferative disorders. SH3TC2 is involved in myelination and maintenance of the node of Ranvier and mutations disturb interactions with the GTPase Rab11. Outside of the peripheral nervous system mutated Rab11 molecules are known to have neoplastic potential through prevention of the normal function of binding the oncogene Evi5, potentially explaining the development of LG as another rare disorder. Despite tenuous links, these rare neurological disorders appear unrelated in this individual.